PARTIAL CHARACTERIZATION OF MIDGUT ENZYMES IN BUTTERFLY PAPILIO POLYTES POLYTES L. (LEPIDOPTERA: PAPILIONIDAE) - S. M. GAIKWAD; G. P. BHAWANE (The Bioscan, 2014)
Characterization of digestive enzymes from the larval and adult midgut of Papilio polytes polytes L. was studied by using different assays. High enzymatic activity were found at pH 7.2 for amylase and invertase, pH 7.8 for trehalase and lipase and pH 9.8 for protease in fifth instar larvae where as it was at pH 6.4 for adult invertase and 400C for all studied enzymes. The linear period of enzyme activities were found at 60, 15, 90, 15 and 20 min for larval amylase, invertase, trehalase, lipase and protease respectively where as it was 30 min for adult invertase. The 50% inhibition at high temperature was found to be 13.5 min (amylase), 9.5 min (invertase), 6 min (trehalase), 8 min (lipase) and 6.5 min (protease) in larva and 6.5 min for adult invertase. The specific activities were 2.844 μg maltose/μg protein/hr, 10.56, 22.25 and 0.4657 μg glucose/μg protein/hr for larval amylase, invertase, trehalase and adult invertase respectively and 9.3474 μg palmitic acid/μg protein/hr (larval lipase) and 1.0285 μg tyrosine/μg protein/hr (larval protease). The measurement of maximal catalytic activities of studied enzymes determines the physiological capacities of the different metabolic pathways. Hence, results of such would be utilized in the formulating control strategies against various pests including the species under study.